The transition from clay to grass in elite junior tennis and the implications on a physical program: a case study - Jones, D. (Journal of Australian Strength and Conditioning, 2012)
Elite tennis players face the challenge of different court surfaces throughout a competitive year. This article focuses on the transition from clay courts to grass courts in three elite junior players. The change in surface has implications on the physiological demands of match play, the style of play, movement demands and injury risk. The varied physical requirements are discussed, as are individual goals and needs of the three athletes. Modifications to the athletes` resistance training programs, on-court training, agility sessions and recovery regimes were made in order to prepare for the change of surface. This included the introduction of specific movement sessions conducted on grass leading into the grass court tournaments, the addition exercises targeting the gluteals and lower back to prepare for the lowered hitting position on grass, modifications to on-court drills and an increased emphasis on post training static stretching during the initial days on grass. The rationale for these modifications and potential impact on performance and injury prevention are also discussed.